2013
DOI: 10.1080/00206814.2013.794915
|View full text |Cite
|
Sign up to set email alerts
|

Re–Os and U–Pb geochronology of porphyry Mo deposits in central Jilin Province: Mo ore-forming stages in northeast China

Abstract: Central Jilin Province lies along the eastern edge of the Xing-Meng orogenic belt of northeast China. At least 10 Mo deposits have been discovered in this area, making it the second-richest concentration of Mo resources in China. To better understand the formation and distribution of porphyry Mo deposits in the area, we investigated the geological characteristics of the deposits and applied zircon U-Pb and molybdenite Re-Os isotope dating to constrain the age of mineralization. Our new geochronological data sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Zhou (2011) summarized the petrogenesis of rocks from 30 different types of deposits and analyzed and collated the range of Re abundances and relative 187 Os abundances, and suggested that Re content might reflect the source of the deposits. The Re abundances of the Houdaomu (43.8-54.2 ppm), Xingshan (20.0-20.4 ppm), Fuanpu (9.9-15.1 ppm), Dashihe (5.6-6.9 ppm), and Jidetun (0.2-0.7 ppm) Mo deposits have been investigated in numerous studies Wang et al, 2009;Ju et al, 2012;Zhou et al, 2013;Zhang et al, 2013). In this study we define the range of Re abundances for the Jiapigou, Shuangshan, Daheishan, Sancha, and Liushengdian Mo deposits to be 52.5-82.6 ppm, 11.3-99.7 ppm, 24.2-43.6 ppm, 15.2-16.4 ppm and 11.9-18.4 ppm, respectively.…”
Section: Re Content and Sources Of The Ore Metalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Zhou (2011) summarized the petrogenesis of rocks from 30 different types of deposits and analyzed and collated the range of Re abundances and relative 187 Os abundances, and suggested that Re content might reflect the source of the deposits. The Re abundances of the Houdaomu (43.8-54.2 ppm), Xingshan (20.0-20.4 ppm), Fuanpu (9.9-15.1 ppm), Dashihe (5.6-6.9 ppm), and Jidetun (0.2-0.7 ppm) Mo deposits have been investigated in numerous studies Wang et al, 2009;Ju et al, 2012;Zhou et al, 2013;Zhang et al, 2013). In this study we define the range of Re abundances for the Jiapigou, Shuangshan, Daheishan, Sancha, and Liushengdian Mo deposits to be 52.5-82.6 ppm, 11.3-99.7 ppm, 24.2-43.6 ppm, 15.2-16.4 ppm and 11.9-18.4 ppm, respectively.…”
Section: Re Content and Sources Of The Ore Metalsmentioning
confidence: 98%
“…1b). Although the geological characteristics and metallogenic chronology of the deposits have been examined previously (e.g., Ge et al, 2007;Li et al, 2009;Wang et al, 2009Wang et al, , 2011Sun et al, 2012;Zeng et al, 2012Zeng et al, , 2013Zhang et al, 2013;Zhou et al, 2013Zhou et al, , 2014, it is unclear whether the ore-forming materials originated from an oceanic plate, the lower crust, or the upper crust. To resolve these questions, we conducted Re-Os isotope dating and analyzed the Re geochemistry of the Mo deposits.…”
Section: Introductionmentioning
confidence: 98%
“…This recorded the transition from the Paleo‐Asian Ocean regime to the circum‐Pacific tectonic regime and the initial subduction of the Paleo‐Pacific Plate (Wang et al ., ). Due to the further subduction during the Middle Jurassic (180–160 Ma), abundant Middle Jurassic calc‐alkaline igneous rocks occur in the central Jilin and eastern Heilongjiang–Jilin regions, marking the peak of magmatism and mineralization induced by the Mesozoic subduction of the Paleo‐Pacific Plate (Zhang et al ., , ; Wang et al ., ; Yang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1970s, more than 10 large porphyry molybdenum, mesothermal hydrothermal lode gold, and magmatic Cu–Ni sulfide deposits have been discovered in this region. Extensive research has been undertaken on these deposits with the goal of documenting their geological characteristics, isotopic ages, ore genesis, and tectonic setting (Wang et al ., ; Zhang et al ., ; Deng et al ., ; Zhang et al ., ; Wang et al ., ). In contrast, the limited Pb–Zn deposits have received less attention (Wang et al ., ; Yang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the EJHP is an ideal area in which to study the Mo‐bearing granitoids and Mo mineralization (Chen, Zhang, Li, Yang, & Deng, ; Ge et al, ; Huang, Chen, Wang, Yuan, & Chen, ; Mao, Wang, Zhang, Yu, & Niu, ; Zeng et al, , ). In the last few years, the geological characteristics of the EJHP have been well documented; many scholars have found that the Mo‐bearing granitoids are dominated by monzogranite, granodiorite, and granite porphyry (Sun et al, ; Yang, Han, Sun, Guo, & Zhang, ; Zhang, Sun, Chen, Zhao, & Gu, ), and these Mo‐bearing granitic rocks were traditionally thought to form in the Mesozoic (Chen, Sun, Pan, Wang, & Huo, ; Chen et al, ; Du et al, ; Ge et al, ; Zeng et al, , ). Although many studies have provided information on the rock association and formation time of those granitoids in the Mo deposits, these are still many unresolved issues remaining to be answered.…”
Section: Introductionmentioning
confidence: 99%